The dynamics of stock market participation - Sigurd Mølster Galaasen; Akash Raja (Norges Bank, 2024)
We document novel facts on the exit and reentry margins of stock market participation by retail investors using detailed administrative data on every Norwegian resident from 1993 to 2016. Contrary to the conventional view that individuals either never or always participate in the stock market, we find that many households leave the stock market within just 2 years of entry. Such behavior is more prominent for people of low income, wealth, and educational attainment, and those of younger age. Estimation of a hazard function shows that there is negative duration dependence in exit probabilities: the longer households participate for, the less likely they are to exit. With respect to the reentry margin, over 30% of exiters subsequently return to the stock market, often just a year later. A structurally-estimated life-cycle model with participation costs fails to generate sufficient exits. Extending the model to allow for experience-based learning, whereby agents form beliefs over the equity premium based on their personal realized returns, improves the model fit of participation rates, conditional risky shares, and financial wealth-toincome ratios by over half, whilst also generating quick exits and a downward-sloping hazard function for exit. However, the model still struggles to generate enough reentry. Using granular portfolio holdings data, we show that poor initial returns are associated with quick exits from the stock market, while positive returns increase the likelihood of reentry in line with an experience effects channel.
hdl:11250/3172114
Keywords: D14; D83; D84; E21; G11; G40; G50; 330; household finance; stock market participation; dynamics; experiences